APLIKASI SISTEM PAKAR IDENTIFIKASI HAMA DAN PENYAKIT SERTA CARA PENGENDALIANNYA PADA TANAMAN KAKAO BERBASIS ANDROID - Aptriani, Rizki; kurniawan, didik; Wibowo, Lestari (Jurnal Komputasi, 2017)
Cocoa (Theobroma cacao L) is one of the plantation commodities that get serious attention because its role is quite high in the national economy. Lampung Province is one of the central cocoa plantations in Indonesia. Cacao cultivation is widely inseparable from a variety of obstacles such as pests and plant diseases. Identification of pests and diseases with various symptoms found in cocoa plants and knowing how to control it is difficult for us, especially farmers in the areas to solve the problem quickly and accurately. Limitations of an expert make handling of pests and diseases of cocoa plants to be difficult, therefore required an expert system that is able to identify pests and diseases in cocoa plants and how to control it based on the knowledge provided by an expert who is able to identify pests and diseases of cocoa and how to control it . This research applied the calculation method of Theorem bayes to calculate the percentage of value. The calculation result is a percentage value and the user can directly see the way pest and disease control are identified. Testing of this research using method Black Box Equivalence Partitioning (EP). Testing questionnaires are divided into 2 variables: user friendly variable and interactive variable. Tests of user friendly variables obtained an average rating of 87.6% and interactive test variables obtained an average rating of 87.52%. With the test results the system shows this app is feasible to use.